Peningkatan Kecerdasan Ekologis Siswa SD melalui Komik Edukasi Berbasis Kearifan Lokal sebagai Sumber Belajar (Studi Etnosains Masyarakat Banjar dan Baduy) - Suhartono Suhartono; Mutiani Mutiani; Akhmad Munaya Rahman; M. Adhitya Hidayat Putra; Cici Murniasih (Departement of Mathematics Education, 2023)
This study aims to: (1) describe the local wisdom of the Banjar community on the banks of the Martapura River, Banjarmasin City and the hinterland of Baduy-Banten; (2) Describe the strategies for increasing the ecological intelligence of students through educational comics as a learning resource. The longterm objective of this research is to build the character of the nation (Nation and Character Building). Through exploring the values ​​of the life of the Banjar people on the banks of the Martapura river, Banjarmasin city and the Baduy-Banten tribe. The value of life of the Banjar and Baduy people who consider the river as a source of livelihood is very potential in shaping identity as a cultured nation through the transformation of character education. The research method used a qualitative approach with ethnoscience study methods. The research subjects were the community, community leaders, students and teachers. The research location is on the banks of the Martapura river, Banjarmasin city and the interior of the Baduy tribe of Banten. The uniqueness referred to is the pattern of life and interaction of people who rely on rivers and land. Collecting data by means of observation, interviews and document studies/ethnoscience. This research is also intended to obtain information about local materials which include local wisdom, local potential and local environmental problems. The results of this study indicate that there are 9 identified local materials that can be used as learning resources, namely the category of local wisdom which includes the habits of the people living at home as a place to live; the community's habit of storing their crops in a shroud; and the custom of the people to protect the river as a source of water for their daily needs. The category of potential/local environmental resources includes the freshwater aquaculture pond ecosystem; tree nurseries, biodiversity, rice field ecosystems; and waste treatment. The results of this study can be a reference for teachers in carrying out thematic learning of local wisdom and can be used as a reference in developing textbooks in the form of educational comics that are sourced from local materials.